Relationship of Knowledge and Addition Food with Increase Weight at Baby 6 – 12 Month - Meilina Estiani; suparno suparno; Nelly Rustiaty (Poltekkes Kemenkes Palembang, 2021)
Background: The delay in providing additional food results in babies suffering from nutritional deficiencies in various forms (Suhardjo, 2013). In OKU District, out of 28,360 children under five were found to have a nutritional status of 1.1%, short toddlers 1.8% and underweight children 0.8% (Dinkes OKU , 2019). Profile of theDinkes OKU, 2019, at the Puskesmas Tanjung Agung , there were 0.1% malnutrition. The Aim of this study was to determine the relationship between knowledge and supplementary feeding with increased body weight in infants aged > 6 months. Methods: The research design is descriptive analytic with a cross-sectional approach. The population is all mothers who have babies over 6 months in DesaTalang Jawa. The sampling technique is accidental sampling. Sample is 31 respondents,. Analysis with chi-square statistical test (95% confidence level, 0.05 significance). Results:Good knowledge of respondents 19.4%, respondents who provide additional food 90.3% and weight gain of children 93.5%. Statistical test : knowledge and supplementary food variables were not associated with weight gain in children ( p value 0.645 and 0.813 ) . Conclusion: There is no relationship between knowledge and supplementary feeding with baby's weight gain.